Nothern Aluminium Enterprise : fixing aluminium, glasses & PVC / Faizal Noh ... [et al.] - Noh, Faizal; Abd Rahman, Muslimah; Abd Rahim, Rozziana; Ramiji, Norhafna (2003)
Partner agreed to form a partnership company, called as NORTHERN ALUMINIUM ENTERPRISE. There are bright futures in the business that we involve. In providing services to customers, we give them to choice what design that they want because we has many aluminum design in our company. Although we get the materials from the distributors, we will always make sure the material is always from high quality standard. Besides giving a high quality standard of material, we also offer a very reasonable price of service to our customer. To give more satisfaction to our customer we only use highly skill workers in doing the decoration and renovation Even though our company still new, with all our effort we will show the best quality of services. We will try to satisfy our customer need by accepting their ideas of decoration. We have our own initiative to change office surrounding and to create a very good mood to the workers. We hope that our business could be widened and simultaneously will open new era and perception in the world of business